468 Team Sport Participation Protects Against Burnout During Neurosurgery Training. (1st April 2022) - Yengo-Kahn, Aaron M.; Grimaudo, Heather C.; Tonetti, Daniel; Burns, Carter; Bonfield, Christopher M.; Dewan, Michael C.; Wellons, John C.; Chitale, Rohan V.; Chambless, Lola B.; Zuckerman, Scott L.
Abstract : INTRODUCTION: Burnout is experienced by up to two-thirds of neurosurgery residents. Team sport participation as an adolescent or young adult has been shown to protect against adverse mental health outcomes (e.g. depression or anxiety) in adulthood. METHODS: A cross-sectional survey study of neurosurgery residents enrolled in U.S. programs was conducted between 6/2020-2/2021. Variables collected through surveys included demographics, weekly exercise, and prior team sport participation, defined as an organized team sport at the high school or collegiate level, even if performed individually (i.e. track/golf). Outcomes included ratings of feelings of sadness, anxiety, stress, burnout, optimism and fulfillment on 100-point scales, with 100 being "I constantly feel this during the day." Individual measures were significantly correlated (r > 0.35, p < 0.0005) and averaged into a composite outcome - "Burnout Composite Score" (BCS). A three-way ANOVA tested the effects of resident level, exercise days and team sport participation on BCS. RESULTS: Of 229 submitted responses, 228 (99.5%) provided complete data. Overall, 185 (81.1%) residents had participated in team sports. Weekly exercise days was similar across groups (2.5±1.8 vs 2.1 ± 1.8, p = 0.20). The team sports group reported lower mean BCS (37.14 vs 43.57, p = 0.030, Cohen's d = 0.369). There was a significant interaction between team sports and exercise regimen on BCS (F(3, 211) = 3.39, p = 0.019, n2 = 0.046). Post-hoc analyses demonstrated more exercise days per week was associated with decreased BCS for prior team sport athletes (F(3, 211) = 11.10, p < 0.0005), but not for non-participants (F(3, 211) = 0.476, p = 0.699). Team sport participation was associated with a larger reduction in BCS among senior residents (11.46 pts, p = 0.016), than junior residents (4.33 pts, p = 0.29). CONCLUSION: Prior team sport participation was associated with lower BCS, an effect more pronounced during senior residency, where residents assume formalized leadership responsibilities. Lessons imparted during early team sport experience may have profound impacts on reducing burnout throughout a seven-year neurosurgery residency.